Packing Performance of Helical Guglielmi Detachable Coil (GDC) 18 in Intracranial Aneurysms: A Comparison with Helical GDC 10 Coils and Complex Trufill/Orbit Coils - Sluzewski, M. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: The purpose of this study was to retrospectively compare the packing performance of helical Guglielmi detachable coil (GDC) 18 (thickness, 0.0135–0.015 inch) with the packing performance of both helical GDC 10 (thickness, 0.010 inch) and complex Trufill/Orbit coils (thickness, 0.012 inch). MATERIALS AND METHODS: From our data base, we selected aneurysms that were exclusively coiled with GDC 18 coils. For every aneurysm treated with GDC 18 coils, we tried to identify a volume-matched control aneurysm treated with exclusively GDC 10 coils or exclusively Trufill/Orbit coils. This process resulted in 32 aneurysm pairs treated with either GDC 18 or GDC 10 coils and 35 aneurysm pairs treated with either GDC 18 or Trufill/Orbit coils. RESULTS: The mean packing of 24.2% of aneurysms treated with GDC 18 was significantly higher than the mean packing of 18.3% of aneurysms treated with GDC 10 (P < .0001). The mean packing of 23.1% of GDC 18 coils was not different from the mean packing of 25.1% of Trufill/Orbit coils (P = .15). CONCLUSION: In aneurysms of 4 mm or larger, packing performance of helical GDC 18 coils is superior to that of helical GDC 10 coils and equal to that of complex Trufill/Orbit coils.